Study of Urban Heat Island of Karachi by Using Finite Volume Mesoscale Model - Sajjad Hussain Sajjad; Nadège Blond; Rabia Batool; Safdar Ali Shirazi; Khadija Shakrullah; M. Nasar Bhalli (Journal of Basic & Applied Sciences, 2015)
Karachi is the largest and most populous metropolitan city of Pakistan and the main seaport and financial centre of the country. Rapid urbanization during last 40 to 50 years caused to accelerate its population to 23.7 million. The objective of this work was to study the impact of urbanization on development of urban heat island (UHI) of Karachi city. The study was conducted by using Finite Volume Mesoscale Model (FVM) in which topography from GTOPO30, land-use from GLC 2000 and Meteorological data from NCEP were used as an input to run the simulation. The simulations were run for three days starting at 00:00 (GMT) on 19th day of April and ending at 00:00 (GMT) on 22nd day of April over selected domain with resolution of 3x3 km of 30 cells. The results showed that there is significance urban heat island presence in Karachi city where the urban area has 5.6°C to 13.5°C higher temperature than its surrounding non-urban areas depending upon the time of a day.